Factors affecting job interview communication competence of unemployed graduates in Malaysia / Masturah Alias - Alias, Masturah (2015)
One of the challenges that graduates faced at job interviews is their inability to communicate competently in English, the language most often used especially at the multinational companies and government-linked companies (GLCs) job interviews. This inability to communicate competently at job interviews is one of the reasons of unemployment among graduates. This study aimed to determine the factors affecting job interview communication competence of unemployed graduates in Malaysia. The present study employed the mixed method research design using questionnaires followed by a semi structured interview with thirteen respondents. The population sample comprised unemployed graduates participating in the SLIM program (Skim Latihan 1 Malaysia) launched by the government to address the unemployment problem among Malaysian graduates. Questionnaires were distributed to 506 unemployed graduates at three participating GLCs in the Klang Valley of which a total of 337 questionnaires were finally used for data analyses. The Job Interview Communication Competence Scale (quantitative instrument) consisted of items on the five factors of communication competence and also those of the dependent variable job interview communication competence. Overall, findings revealed moderate to low levels of general communication skills, context knowledge, English language knowledge and attitude towards the use of English language. Meanwhile, results indicated a moderate to high level of communication apprehension. Findings from qualitative data were found to be congruent with the quantitative data and further affirmed these results. A notable finding in this study seemed to be that general communication skills were very closely and negatively related to communication apprehension as revealed throughout the study in both quantitative as well as qualitative findings. Scores on general communication skills and communication apprehension showed significant relationship with job interview communication competence. The influence of general communication skills and communication apprehension on job interview communication competence was further validated in the final model of the multiple regression analysis where the two factors showed to be the predictors of job interview communication competence. The regression model was used to develop the Five Levels of Job Interview Communication Competence Descriptors to describe job interview communication competence in two ways - as a summary of performance at job interviews and secondly as an overall assessment of abilities in communication. The findings suggested students at the tertiary level may benefit from reinforcement and enrichment of language proficiency and communication skills that can be achieved in English language classes as well as subject area classes designed to facilitate general communication skills and in tandem promotes confidence in students when using the language.